Effects of different phases of menstrual cycle on lung functions in young girls of 18-24 years age - Goyal, Manish; Dwivedi, S. K.; Rajput, Ajit Singh (International Journal of Research in Medical Sciences, 2017)
Background: The dynamic cyclical changes in the levels of various hormones during different phases of menstrual cycle are known to affect functioning of different systems of the body, including the respiratory system. Objective of the study was to study the effects of different phases of menstrual cycle on lung functions in young girls of 18-24 years age. Methods: 78 girls who were medical students of G.R. Medical College, Gwalior, India were chosen for the study. Their lung function parameters were recorded on Spiro Excel, a computerized spirometer. Four lung function parameters i.e. FVC, FEV1, FEV1/FVC% and PEFR were recorded in the different phases of menstrual cycle i.e. menstrual phase, proliferative phase and secretory phase. Results: All lung function parameters except FEV1/FVC% were least in menstrual phase and highest in secretory phase with in between values in proliferative phase. The values were significantly different among the three phases. FEV1/FVC% values were maximum in menstrual phase, lowest in secretory phase with intermediate values in proliferative phase but the values were not significantly different among the three phases. Mean values of FVC, FEV1 and PEFR were higher in all the phases of menstrual cycle in normal BMI subjects as compared to the corresponding phases of underweight subjects. Conclusions: Higher values of lung functions during proliferative and secretory phases can be attributed to the higher concentrations of sex hormones specially progesterone because in most of the studies progesterone is known to cause relaxation of bronchial smooth muscle.